Current Situation and Progress toward the 2030 Health-related Sustainable Development Goals (SDG 3): A Scoping Review in Thailand - Pradidthaprecha, Anunya; Noiwat, Orawan; Bunjongsiri, Kultida (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2023)
By adopting the Sustainable Development Goals (SDGs) in 2015, all of the goals are interconnected, even if only SDG 3 focuses on ensuring healthy lives and promoting wellbeing for all people at all ages. The United Nation member set a number of audacious and ambitious health-related goals that must be accomplished by 2030. While one of the SDGs is “health”, several other “health-related” goals also included. Health-related objectives can serve to direct efforts to promote health, direct health policy, and evaluate progress. A goals-setting process almost always results in a higher focus on illness prevention and health promotion. For Agenda 2030 to be realized, integrated implementation across Goals is required. A multistakeholder, multi-actor response is necessary to implement the 2030 Agenda. In addition to discussion between governments, the commercial sector, civil society organizations, and nongovernmental organizations, innovations and advancement in policy, technology, and research are required. Most significantly, a committed community is required. It is essential to comprehend Thailand’s development toward these goals if population health for 70 million citizens is to be improved. While the body of literature already in existence is replete with normative suggestions for potentially helpful measures, there is less evidence of national implementation plans.